Evaluasi Kualitas Kinerja Widyaiswara Dalam Upaya Peningkatan Kompetensi Pegawai Negeri Sipil (Studi Kasus Badan Pendidikan dan Pelatihan Provinsi Bali) - Diapramana, Made Manggala; Noak, Piers Andreas; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2015)
ABSTRAK The main purpose of National Council for Training and Education of Bali Province is to educate and training government employees peculiarly in province of Bali. As many as 14th Widyaiswara’s have important role in the process of training and education because of that, Widyaiswara’s quality evaluation of occupation in an attempt to improve capabilities of government employees should be realize. This research using descriptive qualitative method which collect the data with observation and interview with analyzing theory. The theory in this research has using human resources theory and specifically the concept of quality evaluation of occupation from Panggabean (2002). According to Panggabean (2002), quality evaluation of occupation should through several processes with identification, observation, measurement and development. The several processes in quality evaluation of occupation will analyzing with PERMENPAN No. 14 tahun 2009 which explain about Functional Position and the Credit Number of Widyaiswara, this process is the mandatory guidelines for Widyaiswara to fulfill duties and collect the credit number for promotion the position of government employees. After this research done, the result can be seen that quality of occupation from Widyaiswara in National Council for Training and Education of Bali Province must be improved within capability and their position. That things happen because Widyaiswara in National Council for Education and Training of Bali nowdays just involved in training and education structurally, which only slightly the technics of training and education from Widyaiswara can get involved. This particularly thing important to increase with Widyaiswara get more active within developing their potential to make their capability became good. The activities for develope their potential can be obtained with colloquium and workshop ; call for paper ; multiplying work hours etc which increasing their capability and credit number to fulfill standart for promotion position. Keywords : Quality Evaluation of Occupation, Widyaiswara’s, PERMENPAN No. 14 tahun 2009